A ten-year search for synchronous cells: obstacles, solutions, and practical applications - Helmstetter, Charles E. (Frontiers in Microbiology, 2015)
My effort to use synchronously dividing cultures to examine the Escherichia coli cell cycle involved a ten-year struggle with failure after failure punctuated by a few gratifying successes, especially at the end. In this essay, I recount my personal journey in this obsessive experimental pursuit. That narrative is followed by a description of a simplified version of the "baby machine," a technique that was developed to obtain minimally disturbed, synchronously growing E. coli cells. Subsequent studies with this methodology led to an understanding of the basic properties of the relationship between chromosome replication and cell division. Accordingly, I end this reminiscence with a simple, fool-proof graphical strategy for deducing the pattern of chromosome replication during the division cycle of cells growing at any rate.